La morale minimale à l’école - Ruwen Ogien (Recherches en Éducation)
All the plans for the reintroduction of moral instruction at school have mixed up the question of the fair with one of the good. The first one concerns ours relationships: to what extent are we respectful, fair, etc.? The second one is to know what are we do of ourselves: the lifestyle that we want to lead, the kind of person that we must be, the ingredients of “good” or “happy” life. Must be a reasonable saver or a big-time gambler? An early riser than tries to do as much as possible or a late riser than tries to do as less as possible? The moralism consists of favouring one of those views of personal good, and all school programs that claim to impose one view of personal good on pupils to the detriment of others is moralist. The minimalist plan tries, as possible, to avoid the moralism at school. It rests on the next principles. In democratic, laic and pluralist school, it’s legitimate to establish the civics, which the purpose is to teach the political institution’s functioning, and to make pupils aware of fair norm, that is, among other things, of the coexistence between persons who have divergent philosophies of life. But, the legitimacy of a compulsory moral education, which the ambition would insert pupils into a “good” or “happy” life, or to pass a certain view of good, or some“values” on to them would be as questionable as education program of a particular religion.